Analisis Pengaruh Winglet Pada Sayap Pesawat Cessna 172 Menggunakan Perangkat Lunak XFLR5 - Bismil Rabeta; Fauzan Taufik Hidayat; Freddy Franciscus (FTK UNSURYA, 2020)
Innovations on aircraft wings always continued in order to achieve better wing efficiency. Especially to optimalization wing shape and reduce induce drag on aircraft by adding device called winglet. This research conduct a study to determine the effect of winglet when adding on Cessna 172 wing. Winglet has a purpose to increase wing’s efficiency by reducing induce drag and increase ratio between lift coefficient and drag coefficient. The test object is modification Cessna 172 wing that modeled with cant angle variation 0°, 30°, 60°, and 90°using software XFLR5. The result shows that wing modification with 30° cant angle winglet has the highest CL/CD ratio about 24,728 with optimum value at 2.5° angle of attack.